Image processing techniques for feature extraction and diagnosis in video-colonscopy - Yang, Xin (2008)
Advances in clinical medical imaging have brought about the routine production of vast numbers of medical images that need to be analysed. As a result, an enormous amount of computer vision research effort has been targeted at achieving automatic analysis of medical images. The study in this thesis is motivated by the fact that during video-colonoscopy, a diagnostic procedure clinically used for cancer detection, the navigation of the endoscope inside the colon requires expert experience and the manual detection of abnormalities leads to variability with various endoscopists.